1944
DOI: 10.3181/00379727-55-14532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rutin on Increased Capillary Fragility in Man.

Abstract: animals to maintain a normal acid-base equilibrium of the blood and to eliminate phenolsulphanephthalein.Structural modification associated with the ageing process which may or may not be designated disease, has resulted in the stabilization of a fundamental equilibrium of the animal organism as the animal relates itself to its normal environment and to an abnormal environment brought about by the introduction of a chemical body foreign to its tissues.Summary. Twenty-three senile dogs showing varying degrees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

1948
1948
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…One of these substances, rutin, has become available recently in pure form. It has been reported to be effective in the treatment of capillary bleeding associated with hypertension in man (13,14), and a recent report (15) indicates that it decreases the incidence of widespread petechiae and ecchymoses in dogs following X-irradiation. Because capillary injury is such a prominent feature in the lesions produced by exposure to severe cold, the effect of rutin was studied on standardized frostbite in rabbits in order to determine the possible prophylactic and/or therapeutic usefulness of this agent.…”
Section: Resultsmentioning
confidence: 99%
“…One of these substances, rutin, has become available recently in pure form. It has been reported to be effective in the treatment of capillary bleeding associated with hypertension in man (13,14), and a recent report (15) indicates that it decreases the incidence of widespread petechiae and ecchymoses in dogs following X-irradiation. Because capillary injury is such a prominent feature in the lesions produced by exposure to severe cold, the effect of rutin was studied on standardized frostbite in rabbits in order to determine the possible prophylactic and/or therapeutic usefulness of this agent.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin is reported to have various effects such as strengthening the blood capillaries [5] [6], as an antioxidant [7]- [9] and to have alpha-glucosidase inhibitory activities [10]. In addition, the clinical effects of rutin in a double-blind crossover study are investigated and reductions in serum myeloperoxidase and cholesterol levels [11], mucosal symptoms, headache, and tiredness are observed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that rutin strengthens fragile blood capillaries (5,6), and has antioxidative (7,8), antihypertensive (9) and a-glucosidase inhibitory activities (10). The clinical effects of rutin-rich food have also been reported; administration leads to reductions in serum myeloperoxidase and cholesterol levels (11), mucosal symptoms, headache and tiredness (11).…”
mentioning
confidence: 99%